Do direct payments efficiently support incomes of small and large farms?. (5th July 2022) - Ciliberti, Stefano; Severini, Simone; Ranalli, Maria Giovanna; Biagini, Luigi; Frascarelli, Angelo
Abstract: This paper assesses how efficiently Common Agricultural Policy direct payments enhance farm incomes by applying a quantile continuous treatment effect model on the Italian Farm Accountancy Data Network sample. Adding to previous analyses, we show that income responses to direct payments are higher in large farms rather than in small farms and lower in farms benefiting from larger levels of support. This suggests that direct payments are not very efficient in supporting incomes of small farms and reducing the disparity existing within the farm population. Furthermore, results suggest that there is scope to reduce the amount of payments provided to highly supported farms.